1993
DOI: 10.1063/1.354152
|View full text |Cite
|
Sign up to set email alerts
|

Dual-ion-beam sputter deposition of ZnO films

Abstract: Physical properties of zinc oxide films deposited by dual-ion-beam sputtering are analyzed to point out the performance of this technique for the deposition of this material. The films are deposited by sputtering a zinc oxide target with an argon-ion beam, while a second low-energy beam, the assistance ion beam, impinges directly on the growing films. Results are presented for ZnO films deposited at room temperature with different oxygen/argon ratios in assistance ion beam and different sputtering ion-beam cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(60 citation statements)
references
References 18 publications
2
53
0
Order By: Relevance
“…The FWHM value of the (002) XRD reflection line, corrected for the instrumental broadening is found to be only 0.15 ° . Together with an optical transmittance above 85% in the visible region with a sharp cut-off at 380 nm and conductivities of around 100 S. cm -1, these properties are amongst the best results reported so far for ZnO layers prepared by any method [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…The FWHM value of the (002) XRD reflection line, corrected for the instrumental broadening is found to be only 0.15 ° . Together with an optical transmittance above 85% in the visible region with a sharp cut-off at 380 nm and conductivities of around 100 S. cm -1, these properties are amongst the best results reported so far for ZnO layers prepared by any method [2][3][4][5][6][7][8][9][10][11][12].…”
Section: Resultsmentioning
confidence: 69%
“…However, the absence of any structure in the shoulders of the Zn 2p3/2 and Zn2pl/2 XPS peaks recorded for these films indicates that they do not contain, within the XPS resolution limit (< 0.1%), metallic Zn. The binding energies of the Ols and Zn2p3/a and Zn2pl/z peaks, measured with respect to that of C ls situated at 284.6 eV, closely correspond to O and Zn in ZnO [8,20] and confirm our previous Rutherford backscattering measurements which showed that the PLD grown films, regardless of the laser employed, were essentially stoichiometric ZnO [13,14]. Narrow XRD lines and refractive index values around 1.97-2.0 were recorded for all the films grown by the KrF laser at fluences in the 1.5-2.5 J/cm 2 range, when keeping substrate temperatures around 300-350°C and oxygen partial pressures in the low 10 .3 Torr range.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ZnO has attracted much attention as varistors [15], piezoelectric devices [16], electroacoustic transducers [17], and highly transparent conducting windows for solar cells, displays [18], vacuum fluorescent displays (VFDs) [19], field emission displays (FEDs) [20], electroluminescent displays (ELDs) [21], UV light-emitting diodes (LEDs), laser diodes [22], and gas sensors [23,24], dye-sensitized solar cells [25][26][27][28][29], and molecular sensors [30].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO thin films have been prepared by different deposition techniques, such as pulsed laser deposition [9], r.f. sputtering [10], molecular beam epitaxy [11], electron beam evaporation [12], chemical vapor deposition [13] and spray pyrolysis [14].…”
Section: Introductionmentioning
confidence: 99%